Workshop on Classroom Action Research and Preparation of Scientific Articles on Research Results in Rupit District North Musi Rawas Regency - Noermanzah, Noermanzah (Journal of Community Research and Service, 2021)
The preparation of classroom action research or CAR and writing scientific articles on research results is still a problem for teachers in Rupit District, North Musi Rawas Regency, South Sumatra Province. For this reason, it is necessary to hold community service by means of classroom action research workshops and the preparation of scientific articles on research results in Rupit District, South Sumatra Province. The purpose of this community service was to describe the results of classroom action research workshops and the preparation of scientific articles on research results in Rupit District, South Sumatra Province. The method of community service is carried out by workshops in which the techniques of lectures, discussions, assignments, and practices are used. The results of the classroom action research workshop and the preparation of scientific research articles for teachers which were carried out in the YP Asra Noman High School Hall, Rupit District, Musi Rawas Utara Regency went well. This is shown from the workshop activities providing understanding to teachers on the preparation of class action research proposals, preparation of classroom action research reports, and the preparation of scientific articles to 22 teachers from elementary, middle, MTs, and high school teachers in the North Musi Rawas area and there are from Musi Rawas Regency. The success of this workshop is not only supported by the school which provides infrastructure as well as resource persons who use discussion methods and assignments or practices, the use of power point media, as well as providing workshop materials and examples of both CAR proposals, CAR reports, as well as scientific journal articles to the participants.